GREEN ACCOMMODATION FOR SUSTAINABLE TOURISM DEVELOPMENT IN MALAYSIA - Bhuiyan, Md. Anowar Hossain; Ismail, Shaharuddin Mohamad (ASEAN Journal on Hospitality and Tourism, 2018)
The study identifies the initiatives of green accommodation in existing policies for achieving sustainable tourism development in Malaysia. It also analyzes the tourists? perception of green accommodation from sustainability perspectives. Non-probability convenience technique has been used for the sample selection and a total of 100 respondents are selected from the tourists by purposive sampling to identified tourists? perceptions. Malaysian policies have emphasized several green strategies in tourist accommodations, such as energy, water, and waste management, introduce renewable energy, build green, environment-friendly and energy conservation buildings, introduce green technologies, reduce greenhouse gas (GHG) emissions, and improve ecological services. The study shows the positive perception of tourists? towards green accommodation which encouraging sustainable tourism development in Malaysia. They agreed that this accommodation is environment-friendly, suitable for resource efficiency, use proper waste management techniques, encourage local products, create employment opportunities for local, promote local culture and traditions as well as ensure well-being for the local communities.